Stourm's Bibliography of the French Finances for the Eighteenth Century (Quarterly Journal of Economics, 1886)
Journal Article Stourm's Bibliography of the French Finances for the Eighteenth Century Get access The Quarterly Journal of Economics, Volume 1, Issue 1, October 1886, Pages 76–80, https://doi.org/10.1093/qje/1.1.76 Published: 01 October 1886